2000
DOI: 10.1038/sj.jhh.1001050
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure patterns and cardiovascular risk factors in rural and urban Gambian communities

Abstract: Hypertension is emerging as an important public health problem in sub-Saharan Africa. We studied blood pressure (BP) patterns, hypertension and other cardiovascular risk factors in a rural and an urban area of The Gambia. A total of 5389 adults (у15 years) were selected by cluster sampling in the capital Banjul and a rural area around Farafenni. A questionnaire was completed, BP, pulse rate, height and weight were recorded. Glucose was measured 2 h after a 75 g glucose load among participants у35 years (n ‫؍‬ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
8
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 14 publications
8
83
8
1
Order By: Relevance
“…Key Words obesity, dyslipidemia, resting energy expenditure , dietary factors Obesity can have many negative effects on health, and is associated with diabetes (1), cardiovascular dis ease (2), hypertension (3), osteoarthritis (4) and dyslipi demia (5). Studies conducted in Sub-Saharan Africa have reported an increase in the prevalence of obesity among both men and women in urban areas (6,7). Other epidemiological surveys in developing countries have shown that an unhealthy diet contributes to the increasing problem of obesity (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Key Words obesity, dyslipidemia, resting energy expenditure , dietary factors Obesity can have many negative effects on health, and is associated with diabetes (1), cardiovascular dis ease (2), hypertension (3), osteoarthritis (4) and dyslipi demia (5). Studies conducted in Sub-Saharan Africa have reported an increase in the prevalence of obesity among both men and women in urban areas (6,7). Other epidemiological surveys in developing countries have shown that an unhealthy diet contributes to the increasing problem of obesity (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we suggested that hypertension control interventions could concentrate on urban populations and on the families of hypertension patients. 24,25 This study adds another perspective on which to focus control activities in areas with a high degree of geographical variation: initial rapid prevalence surveys could enable health officials to target control activities towards higher prevalence communities in their area.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypercholesterolaemia is lowest in rural sub-Saharan Africa (0.1% in rural Gambia and Tanzania) and highest in the more developed urban areas (16.5% in South Africa) [122][123][124]. Mbanya et al [125] reported an absence of hypercholesterolaemia in rural Cameroon.…”
Section: Hypercholesterolaemiamentioning
confidence: 96%